Pertumbuhan dan Hasil Tanaman Sawi Pagoda (Brassica narinosa L.) pada Beberapa Jarak Tanam dan Dosis Pupuk NPK 16-16-16 - Septari, Nita Fadilah; Darma, Wika Anrya; Putri, Sekar Utami; Rahhutami, Ratih (Journal of Horticulture Production Technology, 2025)
Mustard greens are one of the most popular vegetables in Indonesia, leading to an increasing demand each year, though production levels remain unstable. Among its varieties, pagoda mustard (Brassica narinosa L.) has gained popularity due to its nutritional benefits. Proper plant spacing and NPK fertilizer dosage are believed to improve crop yield. This study aimed to: 1) determine the effect of plant spacing on the growth and yield of Pagoda mustard (Brassica narinosa L.), 2) determine the effect of NPK 16-16-16 fertilizer rates on the growth and yield of Pagoda mustard (Brassica narinosa L.), and 3) determine the interaction effect between plant spacing and NPK 16-16-16 fertilizer rates on the growth and yield of Pagoda mustard (Brassica narinosa L.). The research was conducted in Budi Lestari Village, Tanjung Bintang District, South Lampung, from November to December 2024, using a factorial randomized block design with two factors: plant spacing—20 x 20 cm (J1), 30 x 30 cm (J2), and 40 x 40 cm (J3)—and NPK fertilizer dosage—100 kg/ha (N1), 200 kg/ha (N2), and 300 kg/ha (N3). The results showed that a 40 x 40 cm spacing produced the best results for the number of leaves at 28 days after planting, plant dry weight, and root dry weight. A spacing of 20 x 20 cm produced the highest yield per plot. The 200 kg/ha NPK dosage gave the best performance for leaf number, plant dry weight, and root dry weight. The combination of 40 x 40 cm spacing and 200 kg/ha NPK fertilizer resulted in the highest root dry weight.